Research on the Hollow Filter Reactor of Metro Vehicle Electric Drive System - 鲁力; 田奎森; 盛政彬 (机车电传动)
This paper introduced the development of hollow filter reactor of metro electric drive system and puts emphasis on overall structure design, electromagnetic design, key process and test. The solutions had been analyzed and summaried.